A New Approach to Group Decision-Making Method Based on TOPSIS Under Fuzzy Soft Environment - Faruk Karaaslan; Samet Memiş; Serdar Enginoğlu (Journal of New Results in Science)
TOPSIS, developed in 1981 by Hwang and Yoon, is one of the known multi-criteria decision-making (MCDM) methods. In 2015, the group decision-making method based on TOPSIS under fuzzy soft environment was defined and applied to a decision-making problem by Eraslan and Karaaslan. Recently, this method has been configured by Enginoğlu and Memiş via fuzzy parameterized fuzzy soft matrices (fpfs-matrices), faithfully to the original, because a more general form is needed for the method in the event that the parameters have uncertainties. However, the configured method has two drawbacks which affect its running time and the ranking order negatively. We, in this study, improve this method by removing the disadvantages. We then compare the running time of these algorithms. The results show that the new method outperforms it, in particular, a large number of data come into question. For example, the proposed method offers up to 97.7672% of time advantage for ten objects and 9000 parameters. Afterwards, we apply the new method to a performance-based value assignment to seven state-of-art filters used in image denoising, so that we can order them in terms of performance. Finally, we discuss the need for further research.